Congenital Zika syndrome - Israel E. Crisanto-López; Pablo López-De Jesús; Jacqueline López-Quecho; Juan C. Flores-Alonso (Boletín Médico del Hospital Infantil de México, 2023)
In February 2016, the World Health Organization declared Zika virus (ZIKV) infection a public health emergency of international concern because it caused congenital Zika syndrome (CZS). The CZS is considered a specific pattern of birth defects caused by ZIKV infection, which is transmitted by the bite of the Aedes aegypti mosquito. The CZS clinical manifestations are broad and nonspecific, including microcephaly, subcortical calcifications, ocular alterations, congenital contractures, early hypertonia, and pyramidal as well as extrapyramidal symptoms. The ZIKV has gained great importance because it has affected a large percentage of the population worldwide during the last few years, despite the measures implemented by international organizations. The pathophysiology and non-vectorial transmission routes of the virus are still under study. The diagnosis is made upon suspicion of ZIKV infection, the patient’s clinical manifestations, and it is confirmed by molecular laboratory tests demonstrating the presence of viral particles. Unfortunately, there is no specific treatment or vaccine for this condition; however, patients receive multidisciplinary care and constant monitoring. Therefore, the strategies that have been implemented are directed toward preventive measures and vector control.